DARI TRADISIONAL KE MODERN: PENGOBATAN PENYAKIT DI MANGKUNEGARAN AWAL ABAD XX - Handayani, Rinda (Historia, 2024)
This paper discusses the efforts made by the Mangkunegaran government in eradicating disease outbreaks that occurred in the early XX century using both traditional and modern methods. Magkunegaran as a modern kingdom whose initial success came from a sugar factory that had been pioneered since Mangkunegara IV ruled. The economic improvement that was tried to be pioneered turned out to be constrained by the disease outbreak that hit causing casualties. From historical research using document analysis obtained by researchers proves that Mangunegaran has applied both traditional and modern medicine so that disease outbreaks can be resolved. An important conclusion in this research is that Mangkunegaran as a modern kingdom also combines traditional and modern medicine for handling disease outbreaks. Keywords: Mangkunegaran; Medicine; Modern; Traditional